Moderating effects of institutional quality and financial performance on relationship between corporate level determinants of sustainability disclosure compliance in Nigeria - Bello, Mohammed Sabo (2020)
The level of disclosure made by a firm determines the extent of public trust and confidence in the operation of the entity. This study is motivated by the crucial effort made by various regulatory authorities in promoting corporate sustainability disclosure around the world. Thus, this study focuses on the existing discussion on mandatory disclosure compliance with the Corporate Governance Code. The cardinal objective of the study is to investigate some selected firm and board attributes influencing corporate sustainability disclosure compliance (CSDC) in Nigeria. Furthermore, this study aims to examine the moderating effects of institutional quality and financial performance in strengthening the relationship of the firm and board attributes on CSDC in Nigeria. The study measures the extent of disclosure compliance using a total unweighted disclosure index. The sample size of the study comprises of 118 firms listed on the Nigerian capital market. The balanced dataset employed in the study covers a period from the year 2011 to 2017. Companies were selected using a proportionate stratified sampling technique. The dataset is first analysed using the static panel regression analysis by Ordinary Least Square (OLS), Fixed Effect (FE), and Random Effect (RE) models. Subsequently, the regression models are subjected to a further robustness check under the Generalised Method of Moments (GMM) panel regression analysis to test for the possibility of endogeneity in the models. Based on the panel regression analysis, the findings from this study reveal that corporate sustainability disclosure compliance is positive and significantly influenced by industry type, leverage, and board independence. In addition, institutional qualities play a significant role in moderating the relationship between firm attributes and CSDC. This is evidenced based on regression results that show a positive and significant relationship between interactions of corruption control and rule of law with industry type and leverage respectively. Additionally, the findings confirm the moderating effect of financial performance, using return on assets and return on equities as proxies. The set of interactions between return on assets with board size, gender diversity and audit committee shows positive and significant relationships on CSDC. Moreover, interactions between return on equities and board size, board independence and audit committee also reveal a positive and significant finding. The study concludes that the firm and board attributes have significant impact on CSDC. Furthermore, the study presents evidence on the moderating role of institutional qualities and financial performance on the link between firm and board attributes on CSDC. Finally, the study contributes to the existing body of knowledge, policy and practice. Firstly, the findings contribute in advancing the green economics theory within the context of CSDC. Secondly, the study unveils knowledge of the moderating effects of strong institutional quality and financial performance on the extent of CSDC.